The Evenki Memorial Tree and Trail: Negotiating with a Memorial Regime in the North Baikal, Siberia - Simonova, Veronika V. (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2012)
Based upon the ethnography gathered among Evenkis living in Kholodnoye village in the northern coastal area of Lake Baikal in Siberia this article discusses relationships between local memorial practices and official memorial regimes. Although negotiation between authoritative and alternative memories and histories is typically portrayed in terms of resistance, in North Baikal it should be approached differently. Thus Evenkis in alliance with the Taiga creatively engage with official memorial regime in a way local practices of remembering serve positively for the local community. Remembering becomes a 'language' to interact with state powers and external audiences.